Induction motor efficiency maximizing based on torque per power index - Abbas, Najimaldin M.; Mustafa, Mohammed Obaid; Shakor, Ali M. (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
In this paper, efficiency maximization of induction motor variable frequency speed regulation system based on torque per power (TPP) index is proposed. The detail of the mathematical model of the induction motor considering the iron loss and the rotor field orientation, the relationship between the motor torque loss power ratio and the motor speed and slip frequency presented. The functional relationship between the torque loss power ratio and the motor speed and slip is derived, and the derivative is obtained to find the optimal slip frequency corresponding to the maximum value. The simulation model and experimental platform of the control system were built in Matlab/Simulink to verify the effectiveness of the method. The result approved the torque loss power ratio takes the maximum value, the high energy efficiency operation with the minimum power loss of the motor control system is realized.